Fewer guns, more lives: The impact of weapons seizures on homicides in Sao Paulo, Brazil - Felix, Sueli Andruccioli [UNESP]; Damião, Abraão Pustrelo [UNESP] (My University, 2014)
The chapter aims to reflect on the importance of disarmament and criminal dynamics, through the potential and probable deaths prevented from the seizure of firearms by police. Therefore, we carried out a regression analysis involving the guns apprehended by military police in the Metropolitan Region of Sao Paulo, from January 2009 to August 2012, and the total number of homicides (attempted and accomplished) for that period. The results confirm that disarmament lowered homicides by 23%. It is estimated that 23 lives were saved for each group of one hundred firearms apprehended.
Keywords: Brazil; Disarmament; Firearms; Homicide; São paulo